Blogging for dummies - Bair, Amy Lupold; Gardner, Susannah (For dummies, 2014)
The blogosphere keeps changing and evolving, and so does this top blogging guide. A terrific book whether you're just starting out or are already blogging regularly, this book provides solid information on blogging basics, the anatomy of a good blog, and the tools you need to get started. You'll learn how to set up an account, find ample coverage of social plug-ins and emerging platforms like Squarespace and Overblog, and discover savvy ways to write your first post. Best of all, the book explores how you can make real money from your passion and become a professional blogger.